PERAN BADAN USAHA MILIK DESA (BUMDes) DALAM MENDORONG PERTUMBUHAN EKONOMI MASYARAKAT DESA KUTUH KABUPATEN BADUNG - Anak Agung Istri Setiari JMH; Putu Ratna Windusara Putri; I Made Sujana; Ni Luh Wulani Parwati (Yayasan Nusantara Hasana Berdikari, 2024)
Village-Owned Enterprises (BUMDes) are important instruments in rural economic development aimed at improving community welfare through the independent management of local resources. This study aims to analyze the role of BUMDes in promoting economic growth among the community of Kutuh Village, Badung Regency. The research employs a descriptive qualitative approach through a literature review of scientific journals, regulations, and relevant documents concerning BUMDes management in Kutuh Village. The findings indicate that BUMDes in Kutuh Village plays a significant role in increasing village-generated revenue, creating employment opportunities, developing the tourism sector, and empowering local communities through various productive business units. The success of BUMDes in Kutuh Village is supported by strong collaboration among the village government, local community, and customary institutions in managing village resources. Nevertheless, several challenges remain, including the need to improve human resource capacity, business innovation, and adaptation to the digital economy. Therefore, strengthening institutional capacity and enhancing managerial competencies are necessary to ensure the sustainable contribution of BUMDes to rural economic growth.